Genomic evidence of symbiotic adaptations in fungus-associated bacteria - Daniyal Gohar; Kadri Põldmaa; Mari Pent; Saleh Rahimlou; Klara Cerk; Duncan Y.K. Ng; Falk Hildebrand; Mo Bahram (iScience)
Summary: Fungi harbor diverse bacteria that engage in various relationships. While these relationships potentially influence fungal functioning, their underlying genetic mechanisms remain unexplored. Here, we aimed to elucidate the key genomic features of fungus-associated bacteria (FaB) by comparing 163 FaB genomes to 1,048 bacterial genomes from other hosts and habitats. Our analyses revealed several distinctive genomic features of FaB. We found that FaB are enriched in carbohydrate transport/metabolism- and motility-related genes, suggesting an adaptation for utilizing complex fungal carbon sources. They are also enriched in genes targeting fungal biomass, likely reflecting their role in recycling and rebuilding fungal structures. Additionally, FaB associated with plant-mutualistic fungi possess a wider array of carbon-acquisition enzymes specific to fungal and plant substrates compared to those residing with saprotrophic fungi. These unique genomic features highlight FaB’ potential as key players in fungal nutrient acquisition and decomposition, ultimately influencing plant-fungal symbiosis and ecosystem functioning.